Using financial markets information to identify oil supply shocks in a restricted VAR - Marko Melolinna (Bank of Finland, 2008)
This paper introduces a methodology for identifying oil supply shocks in a restricted VAR system for a small open economy. Financial market information is used to construct an identification scheme that forces the response of the restricted VAR model to an oil shock to be the same as that implied by futures markets. Impulse responses are then calculated by using a bootstrapping procedure for partial identification. The methodology is applied to Finland and Sweden in illustrative examples in a simple 5-variable model. While oil supply shocks have an inflationary effect on domestic inflation in these countries during the past decade or so, the effect on domestic GDP is more ambiguous.
URN:NBN:fi:bof-20140807654
Keywords: C01; E32; E44; 330; oil futures; partial identification; macroeconomic shocks